Discussion of “When does the peer information environment matter?” - Matsumoto, Dawn A.; Shaikh, Sarah (Journal of Accounting and Economics, 2017)
Shroff et al. (2017) examine whether a richer peer information environment reduces the cost of capital for firms with limited firm-specific information and whether this effect decreases as firm-specific information becomes more prevalent. Although much of the evidence supporting their hypotheses is based on a small highly idiosyncratic sample of firms issuing initial public debt, the authors provide corroborating evidence using samples of IPO and SEO firms. However, two research design choices make it difficult to discern the nature of the peer information that substitutes for firm information. Hence, the implications of the findings for disclosure regulation are limited.